Aaron Burr conspiracy to treason - Melton, Buckner F. (Wiley, 2002)
Aaron Burr remains one of the most darkly compelling figures in early United States history. Best known as the man who killed Alexander Hamilton in a duel at Weehawken, New Jersey, Burr served as a U.S. senator and as Thomas Jefferson's vice president from 1800 to 1804. Before that, he gained a national reputation as a brilliant attorney. In the first popular book to focus on one of the most intriguing chapters in Burr's long life, historian Buckner F. Melton Jr. explores Aaron Burr's part in one of the most sensational criminal conspiracies in American history. Known as the "Burr Conspiracy," it involved a plan to invade Mexico and set up an independent republic there or, alternately, to get the Western frontiers to cede from the Union and form a separate republic. Although he was ultimately acquitted of the charges against him, Burr was ruined professionally and financially. Melton, who is an acknowledged U.S. constitutional law expert, demystifies the legal issues involved in the case and explores the ethical issues that arose during the trial. He also delves into the relationships lying at the heart of the conspiracy, including those between Burr and Jefferson, Hamilton, and coconspirator General James Wilkinson, commander of the Western United States forces.